Penerapan Arsitektur Neo-Vernakular Pada Desain Sentra Industri Kerajinan Batu Marmer Di Kabupaten Pangkep - Nur, Muhammad Zulhaq; AS, Zulkarnain; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Marble is a type of metamorphic rock, a transitional rock from limestone that changes due to changes in temperature and pressure from endogenous forces. Marble stones are found in caves or mountains in East Java, Aceh, Lampung, West Sumatra, West Java, Central Java, and South Sulawesi. Pangkep Regency in South Sulawesi is a highly productive area for the development of the marble industry. This city has many unique marble mining traditions that will inspire future action. Due to Law No.4/2009 concerning mineral and coal mining, which allows mining companies to process mining products domestically and ban the export of raw materials, only a few marble mines survive to produce marble. So, a center was used to accommodate the processing of marble mining products spread across Pangkep Regency so that they could be exported abroad and increase the selling value of these marble handicraft products. Sourced from several potentials and problems, it is necessary to design a building that becomes a landmark that reflects local culture so that it can become a new icon for Pangkep Regency as a city producing the best marble handicrafts in South Sulawesi.